Differences in Personality Between High-Ability and Average-Ability University Students - Juan Francisco Flores-Bravo; Elena Rodríguez-Naveiras; María de los Dolores Valadez Sierra; Dylan Costantini; África Borges (Journal of Intelligence)
Despite the growing body of research examining the personality traits of individuals with high abilities, little clarity exists about how they differ from the general population, especially within the university context. This study aimed to identify distinct personality traits by examining 268 high-ability university students alongside a matched average-ability group through a retrospective ex post facto design. Results revealed significant differences only in the trait of responsibility (p = 0.037), with lower scores observed among high-ability students. This outcome may be related to specific academic environmental factors, such as insufficient challenges. It can be concluded that, although stereotypes often associate high-ability students with certain personality traits, such as openness to experience, the present results do not reflect such differences. Therefore, it is important to conduct well-designed studies to determine the characteristics of high-ability individuals and how they differ from average-ability students.